2021
DOI: 10.1016/j.cels.2021.08.010
|View full text |Cite
|
Sign up to set email alerts
|

D-SCRIPT translates genome to phenome with sequence-based, structure-aware, genome-scale predictions of protein-protein interactions

Abstract: Highlights d Method to predict protein-protein interactions from primary amino acid sequences d Resulting predictions enable network clustering and functional module detection d Efficient genome-scale PPI prediction helps to tackle the genome-to-phenome problem d Application in bovine rumen reveals links between metabolism and the immune system

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
150
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(175 citation statements)
references
References 104 publications
3
150
0
Order By: Relevance
“…We showed here the limits of classic sequence-based deep learning models for cross-species predictions, but it is worth noting some recent deep learning models that have been successfully used for cross-species predictions [46], [47] by including biological and chemical information about amino acids as well as structural knowledge. The results presented in this work can hopefully guide similar future work and help move this area further.…”
Section: Discussionmentioning
confidence: 97%
“…We showed here the limits of classic sequence-based deep learning models for cross-species predictions, but it is worth noting some recent deep learning models that have been successfully used for cross-species predictions [46], [47] by including biological and chemical information about amino acids as well as structural knowledge. The results presented in this work can hopefully guide similar future work and help move this area further.…”
Section: Discussionmentioning
confidence: 97%
“…In the case of GPCRs, we looked at specificity determining positions (Capra & Singh, 2007;Kalinina et al, 2004), which can then be confirmed by doing 3D structural modeling, to check that the active sites and binding pockets that are expected, should the functional role of the protein be conserved, are indeed present. In the case of G proteins, we derived function based on protein-protein interactions, where we have used our recent deep learning method (Sledzieski et al, 2021) to perform in silico mutagenesis studies to further help us distinguish sequences which are likely to allow us to correctly transfer functional annotation from their human homologs from those that may have other functions. In the case of TLRs, we have used PROSITE to identify presence or absence of entire domains within the sequences, and used expert knowledge to evaluate if the location of these domains matches the functional expectation (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…We took the union of top hits to identify 124 candidate alpha proteins, 207 candidate beta proteins, and 5 candidate gamma proteins. We used the human pre-trained D-SCRIPT (Sledzieski et al, 2021) model to predict interaction between all pairs of alpha-beta, beta-gamma, and alpha-gamma subunits. We performed the same analysis in Montipora capitata (Shumaker et al, 2019), where we identified 184 candidate alpha proteins, 253 candidate beta proteins, and 4 candidate gamma proteins.…”
Section: (D) Transmembrane Helix Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prediction of PPIs is a non-trivial task. Recent tools (Chen et al ., 2019; Hashemifar et al ., 2018) have been found to lack generalisability in predicting PPIs across species (Sledzieski et al ., 2021). Furthermore, most tools were trained and evaluated using specific studies/databases, raising a question of whether these tools are generalisable across studies/databases.…”
Section: Introductionmentioning
confidence: 99%